Developing Observation Report Text Teaching Materials Using Flip HTML5 Application - Unes, Unes; Fithry Muthmainnah; Haris Azhar (MASI Mandiri Edukasi, 2024)
Indonesian language learning implements an independent curriculum, making students the subjects and centers of learning. This curriculum emphasizes developing students' thinking skills in solving problems and projects that can shape character according to the Pancasila student profile and 21st-century skills. In this digital era, education should take advantage of this situation by developing teaching materials, such as converting texts into electronic formats that make it easier for students to access them at school or home. This study aims to produce an e-module of observation report texts for grade X vocational school students. The method used is research and development (R&D) with the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The study results indicate that this e-module is considered very valid by material and media experts and suitable for digital teaching. This e-module can be accessed online, allowing students to learn anytime and anywhere. Expert validation shows that this e-module effectively increases student accessibility and involvement in learning.